Music therapy and neurological rehabilitation : performing health - Aldridge, David, 1947- (J. Kingsley Publishers, 2005)
The central tenet of this innovative collection is that identity can be regarded as a performance, achieved through and in dialogue with others. The authors show that where neuro-degenerative disease restricts movement, communication and thought processes and impairs the sense of self, music therapy is an effective intervention in neurological rehabilitation, successfully restoring the performance of identity within which clients can recognise themselves. It can also aid rehabilitation of clients affected by dementia, traumatic brain injury, and multiple sclerosis, among other neuro-generative.